The Effects of Joint Mobilization and Stretching on the Muscle Activity and Internal Rotation of Shoulder Joint in Patients With Impingement Syndrome With Posterior Shoulder Tightness - Gui-do Moon; Jin-yong Lim; Tae-ho Kim; Dong-woo Lee (Korean Research Society of Physical Therapy, 2020)
Background: Posterior shoulder tightness, which is a problem mainly seen in patients with shoulder impingement syndrome, disrupts the scapulohumeral rhythm between the humerus and scapulae. Objects: The aim of this study was to compare the effects of joint mobilization and stretching on shoulder muscle activity and internal rotation range of motion (ROM) of the glenohumeral joint in patients with impingement syndrome with posterior shoulder tightness. Methods: The research subjects included 22 in-patients with impingement syndrome with posterior shoulder tightness. They were randomly divided into two groups: one group (12 patients) was treated with joint mobilization and the other group (10 patients) was treated with stretching for the posterior shoulder tightness. Each treatment was performed five times a week for two weeks, and there were 15 sessions for each treatment. The ROM of the internal rotation and muscle activities of shoulder joint were evaluated pretest and posttest in each group. Electromyography data were collected from the upper, middle, and lower trapezius and serratus anterior during shoulder abduction of 90°, 120°, and 150°. Results: Both the joint mobilization and stretching groups showed significant decreases in muscle activity in the upper, middle, and lower trapezius on the posttest (p < 0.05). There was a significant difference in serratus anterior at 150° (p < 0.05), but there was no significant difference between group in post-hoc analysis (p > 0.025). The internal rotation ROM was significantly increased in the stretching group compared to that in the joint mobilization group (p < 0.025). Conclusion: This study found that both joint mobilization and stretching for posterior shoulder tightness were effective in muscle activity during arm abduction, also in order to increase internal rotation ROM of shoulder joint, stretching was effective in patients with impingement syndrome with posterior tightness.